Birds Learn to Draw a Variety of Amazing Birds Step by Step - Aaseng, Maury (Califarnia, USA Walter Foster, 2013)
capturing details - rendering textures working with photos - creating dynamic compositions
Arts ( Drawing )
1 13
Keywords: Birds in art; Drawing; Drawing -- Technique